PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN MEREK LGS CASUAL PADA PT MATAHARI DEPARTEMEN STORE MEGA MALL BATAM - Damanik, Rosita; Afridola, Sri (SCIENTIA JOURNAL, 2019)
This thesis uses quantitative research through survey methods to consumers at PT. Matahari Department Store Mega mall Batam. regarding Service Quality and Product Quality affect customer satisfaction. While the data analysis technique used is a method of quantitative analysis, multiple linear analysis and hypothesis testing. The population in this study were as many as 140 consumers. Subjects in the study were consumers of the LGS Casual brand who were respondents. The results of Service Quality research show that the value of t count is 5,101 with a significant level of 0,000 is smaller than 0.05, which means that the hypothesis in this study service quality has a significant effect on Consumer Satisfaction. The results of product quality research shows that the t count value is 5,101 with a significant level of 0,000 is smaller than 0.05, which means that the hypothesis in this study product quality has a significant effect on consumer satisfaction. The results showed F value of 55,079 with a significant level of 0,000 smaller than 0.05 that partially, the variable Service Quality and Product quality had a significant effect on Consumer Satisfaction.